Gender differences in early posttraumatic stress disorder symptoms: a network analysis - Line Rønning; Rachel L. Zelkowitz; Marilyn L. Piccirillo; Jianlin Liu; Jordan L. Thomas; Jessy Guler; J. Joana Kyei; Chris M. Hoeboer; Jeanet F. Karchoud; Miranda Olff; Anke B. Witteveen; Mirjam van Zuiden (European Journal of Psychotraumatology)
Background: Despite known gender/sex differences in the prevalence of posttraumatic stress disorder (PTSD), potential differences in the associations among PTSD symptoms between men and women in the early post-trauma period are not well-characterized.Objective: This study utilized network analysis to assess potential differences in the associations among PTSD symptom clusters between men and women during the early post-trauma period.Method: We included n = 475 participants (57.5% self-identified women) who recently (≤2 months) experienced an interpersonal or motor vehicle potential traumatic event in the Netherlands. Past month PTSD symptoms were measured with the PTSD Checklist for DSM-5 (PCL-5) and composited according to the five-node PTSD symptom cluster dysphoric arousal model. We estimated the network as well as indices of centrality (strength and predictability) and assessed the stability of the modelled networks in subsamples of men (n = 202) and women (n = 273). We compared network structures using the Network Comparison Test (NCT).Results: Results largely demonstrated adequate correlation stability for the estimated network structures for women and men. For both men and women, avoidance symptoms were among the strongest nodes with greatest predictability in the networks. In men, anxious arousal additionally showed high strength whereas re-experiencing showed high predictability. In women, re-experiencing symptoms demonstrated both high strength and predictability. The NCT demonstrated nonsignificant differences in global network structure (M = 0.08, p = .054) and strength (S = .073, p = .067). Post hoc comparisons showed an association of re-experiencing symptoms with negative alterations in cognitions and mood in men but not women (E = .038, p = .005).Conclusion: Results demonstrated possible modest gender differences in aspects of network structure although most elements of the network structure were similar across genders. These results help to characterize gender differences in associations among PTSD symptom clusters during the early post-trauma period, which may inform the potential relevance of future gender-sensitive early intervention strategies to ameliorate the risk for long-term PTSD.